Análisis y Evaluación comparativa de Entrepisos Metálicos ante Vibraciones Generadas por Cargas de Servicio - Morales-Granados, Guillermo (Instituto Tecnológico de Costa Rica, 2010)
This work corresponds to an analysis of service capacity and performance due to the loads producing vibrations induced by people walking on mezzanines with metal structure composed specifically concrete slab on cold formed sections, asbestos cement sheets on profiles and metaldeck system. Particularly, it has been proposed as a starting point for the analysis and comparison of all systems, the analysis of a mezzanine structure for offices, houses or stores. Raised composited slab systems are widely used in our country, however, there is no national reference to address the issue, let alone permissible acceleration values on the severity and frequency to effectively categorize these options on a scale of perception of vibration. This paper uses established testing procedures in the Design Guide called Floor Vibrations due to Human Activity. The above comparison is in terms reasonably similar because they have proposed types of materials, fillers and similar dimensions which allow, at the end, to raise an objective overview of comparison on service capacity and performance of these structures based on values of relative acceleration and frequency.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción).Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2010.
Keywords: Diseño estructural; Estructuras de concreto; Mitigación; Fibrocemento; Capacidad de carga